The Effect of Kluyveromyces Lactis Starter Concentration and Fermentation Time to the Physicochemical and Functional Properties of Egg White Powder - Andry Pratama; Wendry Setiadi Putranto; Kusmajadi Suradi; Robiatul Adawiyah; Risanawati Risanawati; Chintia Ninda (Faculty of Animal Science Universitas Brawijaya, 2019)
The process of making egg white powder would determine the qualities of the product. One way to maintain the qualities of the egg white powder could be done through egg white fermentation prior to drying. This research aims to understand the effect of Kluyveromyces lactis fermentation on egg white at different starter concentrations and fermentation time to the physicochemical and functional properties of the egg white powder. The research is conducted in a completely randomized design experiment with nested treatment. The K. lactis starter concentrations were divided into 3 groups (P1 = 0.2%; P2 = 0.4%; and P3 = 0.6%), and the fermentation times were divided into two groups (W1 = 12 hours; and W2 = 24 hours), with all treatments were repeated four times and nested on the starter concentration. The results showed that concentration K. lactis starter concentration and fermentation time did not give significant effect to the physicochemical and functional (pH, yield, solubility, water, ash, and carbohydrate content, and colours (L*, a*, b*)) properties, but increase the protein content of the egg white powder. The research concludes that egg white fermentation with 0.6% Kluyveromyces lactis concentration for 24 hours gave the best physicochemical and functional properties of the egg white powder.